2012
DOI: 10.1104/pp.112.200154
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Abscisic Acid Signaling Constitutively Activates Arabidopsis Resistance to the Necrotrophic FungusPlectosphaerella cucumerina   

Abstract: Plant resistance to necrotrophic fungi is regulated by a complex set of signaling pathways that includes those mediated by the hormones salicylic acid (SA), ethylene (ET), jasmonic acid (JA), and abscisic acid (ABA). The role of ABA in plant resistance remains controversial, as positive and negative regulatory functions have been described depending on the plant-pathogen interaction analyzed. Here, we show that ABA signaling negatively regulates Arabidopsis (Arabidopsis thaliana) resistance to the necrotrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
136
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(150 citation statements)
references
References 103 publications
(146 reference statements)
10
136
1
3
Order By: Relevance
“…Thus, it was proposed that plants prioritize abiotic stress tolerance over the biotic stress response, with ABA as the molecular switch between the two responses to minimize the damage (Lee and Luan, 2012). Recently, however, contrary studies where biotic stress takes precedence have been reported (Kim et al, 2011;Mang et al, 2012;Sánchez-Vallet et al, 2012). Thus, in light of these recent developments, which revealed a rather complicated picture of multiple stress responses, we embarked on the identification of DEGs in abiotic and biotic stress environments separately and performed comparative analysis of the shared stress-responsive genes, which would provide vital clues on the causative factors behind the cross talk resulting in the observed synergistic and antagonistic regulation of known abiotic and biotic stress response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was proposed that plants prioritize abiotic stress tolerance over the biotic stress response, with ABA as the molecular switch between the two responses to minimize the damage (Lee and Luan, 2012). Recently, however, contrary studies where biotic stress takes precedence have been reported (Kim et al, 2011;Mang et al, 2012;Sánchez-Vallet et al, 2012). Thus, in light of these recent developments, which revealed a rather complicated picture of multiple stress responses, we embarked on the identification of DEGs in abiotic and biotic stress environments separately and performed comparative analysis of the shared stress-responsive genes, which would provide vital clues on the causative factors behind the cross talk resulting in the observed synergistic and antagonistic regulation of known abiotic and biotic stress response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…S8). To date, previous studies of the Arabidopsis-P. cucumerina interaction employed different inoculation methods, which might explain the controversy about the contribution of SA-and ABA-dependent defense against P. cucumerina (Ton and Mauch-Mani, 2004;Sánchez-Vallet et al, 2012;Gamir et al, 2014). Therefore, we urge extra caution when using the Arabidopsis-P. cucumerina pathosystem as a model for studying interactions between plants and necrotrophic fungi.…”
Section: Discussionmentioning
confidence: 95%
“…However, among all these studies, there is increasing controversy about the exact signaling pathways and defense responses contributing to plant resistance against P. cucumerina. While it is clear that JA and ethylene contribute to basal resistance against the fungus, the exact roles of SA, ABA, and ROS in P. cucumerina resistance vary between studies (Thomma et al, 1998;Ton and Mauch-Mani, 2004;Sánchez-Vallet et al, 2012;Gamir et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Arabidopsis plants defective in ABA biosynthesis or signaling exhibit an increased resistance to B. cinerea (Adie et al, 2007). More recently, Arabidopsis mutants impaired in ABA biosynthesis or perception/transduction have been shown to have increased resistance to another necrotrophic fungus, Plectosphaerella cucumerina, as well as constitutive expression of defense responses (Sánchez-Vallet et al, 2012). However, the mechanisms linking a reduced ABA accumulation or perception/transduction to resistance to fungal infection are not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%